The NESH/Abi-3-based WAVE2 complex is functionally distinct from the Abi-1-based WAVE2 complex. Issue 1 (December 2015) - Sekino, Saki; Kashiwagi, Yuriko; Kanazawa, Hitoshi; Takada, Kazuki; Baba, Takashi; Sato, Seiichi; Inoue, Hiroki; Kojima, Masaki; Tani, Katsuko
Abstract Background Abl interactor (Abi) family proteins play significant roles in actin cytoskeleton organization through participation in the WAVE complex. Mammals possess three Abi proteins: Abi-1, Abi-2, and NESH/Abi-3. Abi-1 and Abi-2 were originally identified as Abl tyrosine kinase-binding proteins. It has been disclosed that Abi-1 acts as a bridge between c-Abl and WAVE2, and c-Abl-mediated WAVE2 phosphorylation promotes actin remodeling. We showed previously that NESH/Abi-3 is present in the WAVE2 complex, but neither binds to c-Abl nor promotes c-Abl-mediated phosphorylation of WAVE2. Results In this study, we characterized NESH/Abi-3 in more detail, and compared its properties with those of Abi-1 and Abi-2. NESH/Abi-3 was ectopically expressed in NIH3T3 cells, in which Abi-1, but not NESH/Abi-3, is expressed. The expression of NESH/Abi-3 caused degradation of endogenous Abi-1, which led to the formation of a NESH/Abi-3-based WAVE2 complex. When these cells were plated on fibronectin-coated dishes, the translocation of WAVE2 to the plasma membrane was significantly reduced and the formation of peripheral lamellipodial structures was disturbed, suggesting that the NESH/Abi-3-based WAVE2 complex was unable to help produce lamellipodial protrusions. Next, Abi-1, Abi-2, or NESH/Abi-3 was expressed in v-src -transformed NIH3T3 cells. Only in NESH/Abi-3-expressed cells did treatment with an Abl kinase inhibitor, imatinib mesylate, or siRNA-mediated knockdown of c-Abl promote the formation of invadopodia, which are ventral membrane protrusions with extracellular matrix degradation activity. Structural studies showed that a linker region between the proline-rich regions and the Src homology 3 (SH3) domain of Abi-1 is crucial for its interaction with c-Abl and c-Abl-mediated phosphorylation of WAVE2. Conclusions The NESH/Abi-3-based WAVE2 complex is functionally distinct from the Abi-1-based one, and NESH/Abi-3 may be involved in the formation of ventral protrusions under certain conditions.